Direitos fundamentais atípicos: uma análise do § 2º, do art. 5º, da Constituição Brasileira de 1988 - Santos, Eduardo Rodrigues dos (2015)
The opening clause to new fundamental rights is constitutional den since the dawn of modern constitutionalism, and have positively valued the IX Amendment to the Constitution of the United States of North America in the year 1791. Its importance is latent, especially in hypercomplex societies like contemporary, whose life situations are unpredictable and impossible to be accompanied by positive law in a timely manner, and is therefore covered by several constitutionalism s around the world. In Brazil, was present in all the Republican Constitutions. Provided currently in § 2, art. 5 of the Brazilian Constitution of 1988 provides ample opportunities for recognition of atypical fundamental rights under the paternal constitutionalism. From his further reading can be perceived three sources of recognition of atypical rights: constitutional regime, constitutional principles and international human rights treaties to which Brazil is a signatory. In this paper we analyze all of them in order to identify its meaning in the context of our current constitutionalism. Of the three constitutional sources is possible to identify four possibilities of identification/construction of atypical fundamental rights: fundamental rights in the Constitution expressly positivized but out of the title of fundamental rights; fundamental rights not expressly positivized in the Constitution, but implicitly contained; fundamental rights arising solely from the regime and the principles adopted by the Constitution; fundamental rights arising from international treaties to which the Federative Republic of Brazil is a party. In this paper, we analyze all the possibilities mentioned, aiming to demonstrate the constitutionally correct way to identify/ construct atypical fundamental rights, avoiding that are recognized as fundamental rights which are not, and that it is not recognized as fundamental rights are.